2021
DOI: 10.3390/ijerph18010349
|View full text |Cite
|
Sign up to set email alerts
|

Medical Studies during the COVID-19 Pandemic: The Impact of Digital Learning on Medical Students’ Burnout and Mental Health

Abstract: Objectives: The aim of this ecological study was to investigate what the impact of digital learning due to the COVID-19 pandemic was on the burnout and overall mental health (MH) of medical students. Background: During the unprecedented era of the COVID-19 pandemic, the majority of countries worldwide adopted very strong measures. Universities closed their doors, and education continued through digital learning lectures. Methods: An anonymous questionnaire was administered to all 189 eligible candidates before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
156
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(178 citation statements)
references
References 27 publications
(18 reference statements)
13
156
1
8
Order By: Relevance
“…Our results and comparisons of burnout levels are consistent with the findings of Zis et al 28 that showed no changes in burnout levels when comparing prepandemic and postpandemic data. However, our study had a larger sample, pairing of prequestionnaire and postquestionnaire results, and used two burnout instruments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results and comparisons of burnout levels are consistent with the findings of Zis et al 28 that showed no changes in burnout levels when comparing prepandemic and postpandemic data. However, our study had a larger sample, pairing of prequestionnaire and postquestionnaire results, and used two burnout instruments.…”
Section: Discussionsupporting
confidence: 92%
“…One study found a negative impact of e-learning during lockdown on students’ mental health but no conclusive change in burnout. 28 Another study found that e-learning improved medical students’ mental health and decreased their burnout levels. 29 Findings on medical student satisfaction with e-learning programmes and online teaching are currently mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation, lower motivation, the lack of contacts with peers and teachers, exhaustion from learning on the computer, the lack of physical activity constitute the educational burnout syndrome. The above findings are observed in other studies [25,26]. Different findings indicating a decrease in educational burnout among students during the quarantine have also come to being [27].…”
Section: Discussionsupporting
confidence: 77%
“…The authors suggested that the pandemic crisis will allow enriching dental education with new methods based on modern technologies. Furthermore, Zis et al [33] investigated the impact of digital learning on the burnout and overall mental health of medical students during the COVID-19 pandemic. The burnout prevalence did not differ significantly between the pre-COVID and COVID periods.…”
Section: Discussionmentioning
confidence: 99%